Causality of immune cells on primary sclerosing cholangitis: a bidirectional two-sample Mendelian randomization study - Pu Wu; Pu Wu; Pu Wu; Sinan Xie; Sinan Xie; Sinan Xie; Yunshi Cai; Yunshi Cai; Yunshi Cai; Hu Liu; Hu Liu; Hu Liu; et al. (Frontiers in Immunology, 2024)
BackgroundObservational studies have indicated that immune dysregulation in primary sclerosing cholangitis (PSC) primarily involves intestinal-derived immune cells. However, the causal relationship between peripheral blood immune cells and PSC remains insufficiently understood.MethodsA bidirectional two-sample Mendelian randomization (MR) analysis was implemented to determine the causal effect between PBC and 731 immune cells. All datasets were extracted from a publicly available genetic database. The standard inverse variance weighted (IVW) method was selected as the main method for the causality analysis. Cochran’s Q statistics and MR-Egger intercept were performed to evaluate heterogeneity and pleiotropy.ResultsIn forward MR analysis, the expression ratios of CD11c on CD62L+ myeloid DC (OR = 1.136, 95% CI = 1.032–1.250, p = 0.009) and CD62L-myeloid DC AC (OR = 1.267, 95% CI = 1.086–1.477, p = 0.003) were correlated with a higher risk of PSC. Each one standard deviation increase of CD28 on resting regulatory T cells (Treg) (OR = 0.724, 95% CI = 0.630–0.833, p < 0.001) and CD3 on secreting Treg (OR = 0.893, 95% CI = 0.823–0.969, p = 0.007) negatively associated with the risk of PSC. In reverse MR analysis, PSC was identified with a genetic causal effect on EM CD8+ T cell AC, CD8+ T cell AC, CD28− CD127− CD25++ CD8+ T cell AC, CD28− CD25++ CD8+ T cell AC, CD28− CD8+ T cell/CD8+ T cell, CD28− CD8+ T cell AC, and CD45 RA− CD28− CD8+ T cell AC.ConclusionOur study indicated the evidence of causal effects between PSC and immune cells, which may provide a potential foundation for future diagnosis and treatment of PSC.